Simulation of Military Operation to National Capital City (IKN) Nusantara if Sipadan Island is a Military Base - Kharismaji Kalasmoro; Sobar Sutisna; Syachrul Arief; Agus Haryanto (CV. AFDIFAL MAJU BERKAH, 2023)
Simulation of military operation to national capital city (ikn) nusantara if sipadan island is a military base is aimed to find out the types of military operations that might occur in the future. The military operation used in this simulation are airbone operations, submarine operations, and landing operations. the results of the simulation of the travel time of a fighter aircraft are about 15-38 minutes, where the distance from Sipadan Island to IKN Nusantara is 602 km and the estimated minimum aircraft speed is 950 km/hour and a maximum of 2,500 km/hour. If a beach landing operation is carried out, information is obtained that the shortest distance between Sipadan Island and Sebatik Island is 78.9409 km. if submarine operations are carried out, the ALKI II route is the most suitable path for submarines to traverse where this is obtained from the Indonesian bathymetry map data. Based on the results of this study, the conclusion is that the islands of Sipadan do not and not yet have a potential military threat, but this research can be used as a literature study if in the future the islands of Sipadan begin to be monitored for the construction of military bases.